High Frequency Rapid Plant Regeneration from Shoot Tip and Nodal Explants of Mentha piperita (L.) – An Important Multipurpose Medicinal Plant - C.V. Naidu2*, P. Sujana1 and (Journal of Phytology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Mentha piperita<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> L. (Peppermint) is a perennial glabrous and strongly scented herb belonging to the family lamiaceae. The plant is aromatic, stimulant, and used for allaying nausea, headache and vomiting.Ã‚Â <span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: MinionPro-Cn; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Peppermint raw material is used in medicine, cosmetics and food industry, therefore this plant is widely grown around the world. Peppermint produces a large amount of essential oils and has a good aroma, thus it is more widely grown, especially for industrial processing. <span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">An in vitro regeneration system with a maximum efficiency rate was developed in Mentha piperita using shoot tip and nodal segments of three week old stock plants on Murashige and SkoogÃ¢â‚¬â„¢s (MS) medium supplemented with combination of 6- benzyl amino purine and naphthalene acetic acid (BAP - 1.5mg/L and NAA - 0.1 mg/L). Shoots developed at sites of excision directly from the cells. The highest numbers of shoots (53) were obtained on medium containing BAP and NAA. In vitro shoots were then excised from the shoot clumps and transferred to rooting medium containing indole butyric acid (IBA - 1.5 mg/L). The rooted plantlets were hardened in polythene cups containing sterile soil and vermiculite (1:1). Plantlets thus developed were successfully established and finally transferred to a greenhouse. The present regeneration system is highly reproducible and the regenerated plants developed normally and were phenotypically similar to the parent plant.